Critical review of the theories of economic integration regional (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
Explain the process of regional economic integration and how they should be carried out has been analyzed by different authors for many years , so there is no single theoretical explanation of the integration processes , however , this issue has been used by different schools of thought and each presented their ideas about how it should be addressed .In practice there are different schemes of regional integration , the EU considered the most forward . In the case of Latin America , integration shows less success , despite being a long-standing process .This essay takes a tour of the various theories that attempt to explain this phenomenon , in order to make a critical review based on their approaches and what happened in the real world.Methodological review of different authors is performed to ascertain the contributions of each of the theories and then compare them with empirical evidence , especially in the case of Latin America. We conclude that under the conditions of these countries , the process of integration in this region should be based on the proposals of the Latin American structuralist school.
Keywords: economic integration; theoretical basis; critical review; Latin America